The Influence of Collaborative Strategies in Promoting Increasing Sales Volume of Creative Industry MSMEs - Nabila Az Zahrah (Universitas 45 Surabaya, 2024)
This research seeks to gain a comprehensive interpretation of the collaborative strategies enforced by Micro, Small, and Medium Enterprises (MSMEs). By using a qualitative analysis approach with a descriptive framework, this research utilizes SWOT analysis as an important tool for identifying variables in formulating organizational strategy. The findings of this analysis underscore the importance for MSMEs operating in the creative industries to carefully assess their internal strengths and weaknesses, as well as external opportunities and threats, to effectively navigate increasingly fierce market competition. In particular, the intrinsic strengths of MSMEs, characterized by creativity and adaptability, play an important role in product differentiation and attracting consumer interest. Nevertheless, the challenges posed by financial constraints and limited global market access require strategic mitigation. Opportunities arising from market expansion initiatives and the strategic use of information technology provide opportunities to increase the prospects for the success of MSMEs. However, increasing awareness of competitive pressures and potential risks while maintaining product quality remains paramount. Through SWOT analysis, MSMEs can design tailored strategies to increase their competitive advantage and ensure business sustainability. Creative initiatives such as leveraging social media platforms, forging partnerships with local suppliers and artists, driving product innovation, providing exceptional customer service, and diversifying sales channels are emerging as critical enablers to increase sales volumes and achieve success amidst a highly competitive market landscape.